Longitudinal analysis of SARS-CoV-2 infection and vaccination in the LA-SPARTA cohort reveals increased risk of infection in vaccinated Hispanic participants - Jenkins, Meagan M.; Phan Tran, Donna; Flores, Evelyn A.; Kupferwasser, Deborah; Pickering, Harry; Zheng, Ying; Gjertson, David W.; Ross, Ted M.; Schaenman, Joanna M.; Miller, Loren G.; Yeaman, Michael R.; Reed, Elaine F. (Frontiers in Immunology, 2023)
SARS-CoV-2 is the etiologic agent of coronavirus disease 2019 (COVID-19). Questions remain regarding correlates of risk and immune protection against COVID-19. We prospectively enrolled 200 participants with a high risk of SARS-CoV-2 occupational exposure at a U.S. medical center between December 2020 and April 2022. Participant exposure risks, vaccination/infection status, and symptoms were followed longitudinally at 3, 6, and 12 months, with blood and saliva collection. Serological response to the SARS-CoV-2 spike holoprotein (S), receptor binding domain (RBD) and nucleocapsid proteins (NP) were quantified by ELISA assay. Based on serology, 40 of 200 (20%) participants were infected. Healthcare and non-healthcare occupations had equivalent infection incidence. Only 79.5% of infected participants seroconverted for NP following infection, and 11.5% were unaware they had been infected. The antibody response to S was greater than to RBD. Hispanic ethnicity was associated with 2-fold greater incidence of infection despite vaccination in this cohort. Overall, our findings demonstrate: 1) variability in the antibody response to SARS-CoV-2 infection despite similar exposure risk; 2) the concentration of binding antibody to the SARS-CoV-2 Spike or RBD protein is not correlated with protection against infection in vaccinated individuals; and 3) determinants of infection risk include Hispanic ethnicity despite vaccination and similar occupational exposure.